Participatory action research to co-design a culturally appropriate COVID-19 risk communication and community engagement strategy in rural Pakistan - Moran, Victoria Hall; Ceballos-Rasgado, Marena; Fatima, Sadia; Mahboob, Usman; Ahmad, Salman; McKeown, Michael; Zaman, Mukhtiar (Frontiers in Public Health, 2023)
Background: Community engagement has shown to be fundamental component of the response to previous disease outbreaks. This study aimed co-design and implement a culturally appropriate COVID-19 risk communication and community engagement strategy with a resource-poor rural community in Northwest Pakistan. Methods: Participatory Action Research (PAR) was conducted from January 2021 to March 2022. Five PAR meetings took place with community members (n=30) to: 1) explore how the COVID-19 pandemic impacted on the community; 2) identify challenges to limit the spread of the virus; 3) identify and implement solutions to these challenges; and 4) highlight the enablers, challenges and knowledge of the cultural context needed to optimize safety during emergencies. Focus group discussions (N=6) with community members not involved in the PAR meetings (N=50) and children of the community (N=26) were conducted following the PAR meetings. Thematic analysis of the PAR and focus group data was conducted. Results: Delivery of messages on how to keep families safe, provision of personal protective equipment and improved water systems were part of the strategies taken by the community to create awareness and reduce the spread of COVID-19. Nine themes were identified: Attitudes to the pandemic: From skepticism to acceptance, changing attitudes about vaccination: rumors and trust, COVID-19 and Faith, Social impact of the pandemic, Access to water, Resource mobilization: personal protective equipment, Spaces where collaborative effort can bring to solutions, Agents of change, and Empowerment of women. Discussion: The participatory approach of this research allowed understanding of the challenges faced by the community to engage in behavior change strategies to reduce the spread of COVID-19 and enabled the community to find sustainable solutions. Engagement with the community empowered men and women to be agents of change and promoted necessary precautionary actions to reduce the risk of infection within their community. Conclusions: Participatory approach highlighted the importance of engaging with and integrating to local culture and values to overcome challenges such as gender imbalance and distrust. Findings of this study are relevant to others working in diverse cultural settings in similar crises events regardless of particular cultural variations.